Polymer‐Based Ruthenium(II) Polypyridyl Chromophores on TiO2 for Solar Energy Conversion. Issue 8 (17th March 2016) - Leem, Gyu; Morseth, Zachary A.; Wee, Kyung‐Ryang; Jiang, Junlin; Brennaman, M. Kyle; Papanikolas, John M.; Schanze, Kirk S.
Abstract: A polychromophoric light‐harvesting assembly featuring a polystyrene (PS) backbone with ionic carboxylate‐functionalized Ru II polypyridyl complexes as pendant groups (PS‐Ru‐A) was synthesized and successfully anchored onto mesoporous structured TiO2 films (TiO2 //PS‐Ru‐A). Studies of the resulting TiO2 //PS‐Ru‐A films carried out by transmission electron microscopy (TEM), scanning electron microscopy (SEM), and atomic force microscopy (AFM) confirmed that the ionic carboxylated Ru II complexes from PS‐Ru‐A led to the surface immobilization on the TiO2 film. Monochromatic light photocurrent spectroscopy (IPCE) and white light (AM1.5G) current–voltage studies of dye‐sensitized solar cells using the TiO2 //PS‐Ru‐A photoanode give rise to modest photocurrent and white light efficiency (24 % peak IPCE and 0.33 % PCE, respectively). The photostability of surface‐bound TiO2 //PS‐Ru‐A films was tested and compared to a monomeric Ru II complex (TiO2 //Ru‐A), showing an enhancement of ∼14 % in the photostability of PS‐Ru‐A. Transient absorption measurements reveal that electron injection from surface‐bound pendants occurs on the picosecond time scale, similar to TiO2 //Ru‐A, while time‐resolved emission measurements reveal delayed electron injection occurring in TiO2 //PS‐Ru‐A on the nanosecond time scale, underscoring energy transport from unbound to surface‐bound complexes. Additionally, charge recombination is delayed in PS‐Ru‐A, pointing towards intra‐assembly hole transport to complexes away from the surface. Molecular dynamics simulations of PS‐Ru‐A in fluid solution indicate that a majority of the pendant Ru II complexes lie within 10–20 Å of each other, facilitating efficient energy‐ and charge transport among the pendant complexes. Abstract : A novel polystyrene‐based assembly containing pendant Ru II polypyridyl complexes (PS‐Ru‐A) was immobilized covalently to mesoporous TiO2 films. The PS‐Ru‐A adsorbed TiO2 films improve the photostability, efficient light absorption, energy transfer and charge transport to/from the interface in comparison to a monomeric Ru II chromophore.